2017
DOI: 10.1080/17441692.2017.1385823
|View full text |Cite
|
Sign up to set email alerts
|

Integration of tuberculosis and HIV services: Exploring the perspectives of co-infected patients in Ghana

Abstract: Scaling up of integrated tuberculosis (TB)-human immunodeficiency virus (HIV) services remains sub-optimal in many resource-limited countries, including Ghana, where the two conditions take a heavy toll on the financial resources of health systems as well as infected persons. Previous studies have documented several implementation challenges towards TB-HIV service integration, but views of patients on integrated service delivery have not received commensurate research attention. This paper explored the experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Despite the increasing burden of disease derived from TB and NCDs in LMICs and the need for TB and NCD integrated programmes, most systematic reviews on TB service integration investigate the integration of TB- and HIV-related services or the health outcomes of TB and NCD comorbidities, their syndemic interactions, and prevalence [ 25 34 ]. Therefore, there remains a dearth of information regarding the mechanism of integration of TB and NCDs related services in LMICs, which this systematic review aims to address.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing burden of disease derived from TB and NCDs in LMICs and the need for TB and NCD integrated programmes, most systematic reviews on TB service integration investigate the integration of TB- and HIV-related services or the health outcomes of TB and NCD comorbidities, their syndemic interactions, and prevalence [ 25 34 ]. Therefore, there remains a dearth of information regarding the mechanism of integration of TB and NCDs related services in LMICs, which this systematic review aims to address.…”
Section: Introductionmentioning
confidence: 99%
“…She found that NPT assisted in identifying the social influences and HCP attributes that affected patient responses to the offer of NHS Health Checks [ 38 ]. Anku et al [ 39 ] similarly included patients, as well as practitioners and providers, in their study of combining tuberculosis and HIV services in Ghana. Understanding both the patient perspective and the environment at every level is critical in understanding the overall normalizing of an intervention [ 21 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…These challenges can, however, be addressed through service delivery in a better integrated (more complex) system [28]. There is evidence to show that full integration of TB-HIV services is considered most appropriate and acceptable among clients, especially co-infected clients [32].…”
Section: Discussionmentioning
confidence: 99%